Euconnus franzi Asenjo, new name on Neotropical Euconnus Thomson (Coleoptera: Staphylinidae: Scydmaeninae: Glandulariini) - Asenjo, Angélico (Zootaxa, 2016)
During my doctoral studies, while assembling a taxonomic list of the Staphylindae of Brazil (Asenjo et al. 2013: 229), I found a primary junior homonym in the genus Euconnus Thomson. The purpose of this note is to provide a correction to this problem.